Analyzing the potential and development of sustainable tourism in Kampoeng Lama Tourism Village, North Sumatra - Nasution, Rahmi Khairani; Harahap, R. Hamdani; Kurniawati, Dewi; Ridho, Hatta (Edelweiss Applied Science and Technology, 2025)
This study aims to examine the potential and development of sustainable tourism in Kampoeng Lama Tourism Village, North Sumatra, by assessing its economic, social, and environmental dimensions. A mixed-methods approach with an explanatory sequential design was employed, beginning with a quantitative survey of 94 domestic tourists, followed by qualitative interviews with 10 key stakeholders. Analytical tools including Multidimensional Scaling (MDS) and Monte Carlo simulations were used to evaluate sustainability indicators. The findings reveal that Kampoeng Lama demonstrates strong social and environmental sustainability, characterized by active community participation, ecosystem-based attractions, and well-preserved landscapes. However, the economic dimension remains moderately sustainable, limited by inadequate infrastructure, low digital readiness, and fragmented institutional capacity. Key attractions such as Sanggar Lingkaran, Paloh Naga Agrotourism, and PASAR KAMU highlight local innovation in tourism. The typical tourist profile—young, educated, and local—suggests the need for more diverse tourism packages and service improvements. In conclusion, the study underscores the importance of integrated, community-driven governance involving BUMDes, Pokdarwis, and village stakeholders. Practical implications point to the need for increased infrastructure investment, improved environmental management, and stronger inter-sectoral partnerships to enhance long-term sustainability in rural tourism development.